Knowing the signs, changing the outcome: educational impact of the mother and child health handbook on high-risk mothers - Angela, Nabila Fitria; Suptiani, Laila Putri; Purnamasari, Wiwin Mintarsih (Poltekkes Kemenkes Yogyakarta, 2024)
particularly in low- and middle-income countries. One contributing factor is the lack of maternal awareness regarding pregnancy danger signs. Although the Mother and Child Health (MCH) handbook has been widely distributed in Indonesia to support maternal education, its utilization remains suboptimal. This study aims to assess the effectiveness of a structured educational intervention using the MCH handbook on improving the knowledge of high-risk pregnant women regarding pregnancy danger signs. This pre-experimental study employed a one-group pretest-posttest design involving 58 high-risk pregnant women at Cibeureum Public Health Center, Tasikmalaya, Indonesia. Participants' knowledge was measured before and after an educational intervention using the MCH handbook. A paired t-test was conducted to analyze the statistical significance of changes in knowledge scores. The normality of the data was confirmed using the Shapiro-Wilk test. The mean knowledge score significantly increased from 19.00 (SD = 3.10) before the intervention to 24.91 (SD = 0.28) after the intervention (mean difference = 5.91, p < 0.001). Prior to the intervention, 74.14% of participants had high knowledge, 17.24% moderate, and 8.62% low. After the intervention, 100% of participants attained high knowledge levels. The findings suggest that structured health education using the MCH handbook is highly effective in enhancing maternal knowledge, especially among high-risk pregnant women. This reinforces the importance of integrating systematic MCH handbook-based education into routine antenatal care. Utilizing the MCH handbook as a structured educational tool significantly improves maternal awareness of pregnancy danger signs. Strengthening health worker capacity to deliver MCH handbook-based education and promoting its use during ANC visits may contribute to earlier risk detection and reduction of maternal mortality.